Functional Variants Surrounding Endothelin 2 Are Associated With Mycobacterium avium Subspecies paratuberculosis Infection - Kiser, Jennifer N.; Wang, Zeping; Zanella, Ricardo; Scraggs, Erik; Neupane, Mahesh; Cantrell, Bonnie; Van Tassell, Curtis P.; White, Stephen N.; Taylor, Jeremy F.; Neibergs, Holly L. (Frontiers in Veterinary Science, 2021)
Bovine paratuberculosis, caused by Mycobacterium avium subspecies paratuberculosis (MAP), continues to impact the dairy industry through increased morbidity, mortality and lost production. Although genome-wide association analyses (GWAA) have identified loci associated with susceptibility to MAP, limited progress has been made in identifying mutations that cause disease susceptibility. A 235 kb region on Bos taurus chromosome 3 (BTA3), containing a 70 kb haplotype block surrounding endothelin 2(EDN2) has previously been associated with the risk of MAP infection. EDN2 is highly expressed in the gut and is involved in intracellular calcium signaling and a wide array of biological processes. The objective of this study was to identify putative causal mutations for disease susceptibility in the region surrounding EDN2 in Holstein and Jersey cattle. Using sequence data from 10 Holstein and 10 Jersey cattle, common variants within the 70 kb region containing EDN2 were identified. A custom SNP genotyping array fine-mapped the region using 221 Holstein and 51 Jersey cattle and identified a SNP in the 3’ UTR (P = 0.00009) plus 17 putative causal variants (P < 0.01) located in the 5’ region of EDN2 and a SNP in the 3’ UTR (P = 0.00009) associated with MAP infection. MicroRNA interference assays, mRNA stability assays, and electrophoretic mobility shift assays were performed to determine if allelic changes at each SNP resulted in differences in EDN2 stability or expression. Two SNPs (rs109651404 [G/A] and rs110287192 [G/T]) located within the promoter region of EDN2 displayed differential binding affinity for transcription factors in binding sequences harboring the alternate SNP alleles. The luciferase reporter assay revealed that the transcriptional activity of the EDN2 promoter was increased (P < 0.05) with the A allele for rs109651404 and the G allele for rs110287192. These results suggest that the variants rs109651404 and rs110287192 are mutations that alter transcription and thus may alter susceptibility to MAP tissue infection in Holstein and Jersey cattle.